1996
DOI: 10.1164/ajrccm.153.2.8564110
|View full text |Cite
|
Sign up to set email alerts
|

Elevated TNF-alpha production by peripheral blood monocytes of weight-losing COPD patients.

Abstract: The inflammatory cytokines, tumor necrosis factor-alpha (TNF-alpha) and interleukin-1-beta (IL-1 beta), have been associated with accelerated metabolism and protein turnover following exogenous administration in normal humans. We hypothesized that these inflammatory cytokines might contribute to the weight-losing process in patients with chronic obstructive pulmonary disease (COPD). COPD patients were identified prospectively as "weight losers" (WL; n = 10) if they reported > 5% weight loss during the precedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
169
5
10

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(192 citation statements)
references
References 0 publications
8
169
5
10
Order By: Relevance
“…It is line with studies showing relationship between losing weight and serum TNF-α in COPD [8,12,15,37]. Alteration of FEV1 values might not be strictly related to change in airway calibre but may also depend on pulmonary elastolysis and reduced respiratory skeletal muscle forces, both processes likely to be influenced by TNF-α [6,15].…”
Section: Discussionsupporting
confidence: 85%
“…It is line with studies showing relationship between losing weight and serum TNF-α in COPD [8,12,15,37]. Alteration of FEV1 values might not be strictly related to change in airway calibre but may also depend on pulmonary elastolysis and reduced respiratory skeletal muscle forces, both processes likely to be influenced by TNF-α [6,15].…”
Section: Discussionsupporting
confidence: 85%
“…Stimulation of the bone marrow by cigarette smoke is probably mediated by soluble factors released from the lung. Alveolar macrophages are an important source of pro-inflammatory soluble factors and when stimulated by cigarette smoke produce factors such as TNF-a, IL-1, IL-8 and GM-CSF [13,14]. These factors are capable of stimulating haematopoietic precursors in the marrow and cause the release of granulocytes from the bone marrow into the circulation [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…In previously reported animal studies, it was found that cigarette smoke exposure accelerated the release of PMNLs from the bone marrow, which was postulated to be mediated by soluble factors released from the lung [12]. Alveolar macrophages are an important source of pro-inflammatory mediators and, when stimulated by cigarette smoke, produce factors such as tumour necrosis factor-a (TNF-a), interleukin (IL)-1, IL-6, IL-8 and haematopoietic growth factors such as granulocyte-macrophage colony-stimulating factor (GM-CSF) and granulocyte colony-stimulating factor (G-CSF) [13,14]. When these factors circulate they are capable of stimulating haematopoietic precursors resulting in accelerated proliferation and release of PMNLs from the bone marrow into the circulation [15,16].…”
mentioning
confidence: 99%
“…Tumour necrosis factor-a Plasma tumour necrosis factor (TNF)-a and its soluble receptor are increased in COPD patients [13][14][15], and TNF-a is also released from circulating cells in COPD patients with cachexia [16]. Circulating TNF-a appears to be related, at least in part, to hypoxaemia [14].…”
Section: Interleukin-6mentioning
confidence: 99%